Future Trends in Cervical Spinal Fusion Surgery Through 2035 Among the US Medicare Population - Tarun Mattikalli; Matthew T. Carr; Jeremy Steinberger; Konstantinos Margetis (Clinical Spine Surgery, 2026)
Study Design: Retrospective cohort study. Objective: This study aimed to forecast national trends in anterior cervical discectomy and fusion (ACDF) and posterior cervical fusion (PCF) through 2035 in the US Medicare population using comprehensive, procedure-specific modeling approaches. Summary of Background Data: Cervical spinal fusion is widely performed for degenerative cervical spine disease. ACDF remains the most common procedure, while PCF is indicated for multilevel disease, deformity, and revision cases. Despite the high-utilization, up-to-date, procedure-specific forecasts for the Medicare population are lacking. Updated forecasts are required to guide workforce planning, policy development, and resource allocation for an aging population. Methods: National Medicare Part B data were analyzed from 2005 to 2022 to identify ACDF and PCF procedures using Current Procedural Terminology (CPT) codes. Procedure volumes were adjusted for Medicare Advantage enrollment. Ordinary least squares (OLS) regression models were developed to project volumes through 2035, excluding data from 2020 and 2021 to minimize bias from COVID-19-related disruptions. Model performance was assessed using R 2 , slope estimates, and 5-fold cross-validation. Results: Estimated ACDF volumes increased from 57,765 in 2011 to 101,019 in 2022. ACDF volumes are projected to increase to about 170,102 procedures by 2035 (95% CI: 139,912–200,291). Estimated PCF volumes increased from 9659 in 2005 to 42,400 in 2022 and are projected to reach 68,901 procedures by 2035 (95% CI: 66,108–71,693). The models demonstrated strong fit for both procedures (ACDF R 2 =0.8382, PCF R 2 =0.9892). Conclusions: National volumes of cervical spinal fusion are expected to continue rising through 2035 among Medicare beneficiaries. These trends likely reflect an aging population, broader surgical indications, and the continued shift toward outpatient spine surgery. Our findings have important implications for surgical workforce needs, reimbursement policy, and resource allocation across inpatient and ambulatory care settings.